ANALISIS PERUMUSAN STRATEGI BAGI PT RAMAYANA LESTARI SENTOSA, TBK - Yoseph Mario Leonard (Politeknik Ubaya, 2023)
The retail industry sector is one of the industries affected by the Covid-19 pandemic in Indonesia, including Ramayana. This was marked by a significant decrease in Ramayana's revenue during the Covid-19 pandemic and until now Ramayana's condition has not been able to return to the company's best performance before the Covid-19 pandemic in Indonesia. In addition, Ramayana does not only focus on serving customers in the class C and class D economy segments, but wants to serve a new segment, namely the class B economy segment. Therefore, the purpose of this study is to formulate the right strategy for PT Ramayana Lestari Sentosa, Tbk based on this phenomenon. The research was conducted using a qualitative approach. Data collection techniques were carried out by observing and using the literature review method. The theory that has been described in the theoretical basis section is then applied to PT Ramayana Lestari Sentosa, Tbk. to support research on appropriate strategies. The data used in this study is secondary data sourced from company annual reports. The results of the research show that the strategy proposed in Ramayana is product development.